2013
DOI: 10.1007/s12272-013-0108-4
|View full text |Cite
|
Sign up to set email alerts
|

3EZ,20Ac-ingenol, a catalytic inhibitor of topoisomerases, downregulates p-Akt and induces DSBs and apoptosis of DT40 cells

Abstract: We have previously reported that many ingenol compounds derived from Euphorbia kansui exhibit topoisomerase (topo) II inhibitory activity. Of these compounds, 3EZ,20Ac-ingenol inhibited topo I activity. Camptothecin, which inhibits the religation activity of topo I without interfering with the binding of topo I to DNA and induces topo I-mediated DNA cleavage, was used as a positive control. In this study, we found that 3EZ,20Ac-ingenol did not hamper the binding of topo I to DNA in the same manner as camptothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The topoisomerase I catalytic inhibitors, betulinic acid and ␤-lapachone, have also been studied extensively as cancer drugs, and although several studies reported that they induce PI3K/Akt inactivation [32,33], their ensuing apoptotic mechanisms remain unclear. We also reported previously that the catalytic topoisomerase I inhibitor 3EZ, 20Ac-ingenol induced DNA damage leading to apoptosis via Akt inactivation in B cell line, DT 40 [24]. PTEN deficient cells have higher genomic instability suggesting that PTEN modifies chromatin structure and thereby influences the repair of DNA damage [34].…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…The topoisomerase I catalytic inhibitors, betulinic acid and ␤-lapachone, have also been studied extensively as cancer drugs, and although several studies reported that they induce PI3K/Akt inactivation [32,33], their ensuing apoptotic mechanisms remain unclear. We also reported previously that the catalytic topoisomerase I inhibitor 3EZ, 20Ac-ingenol induced DNA damage leading to apoptosis via Akt inactivation in B cell line, DT 40 [24]. PTEN deficient cells have higher genomic instability suggesting that PTEN modifies chromatin structure and thereby influences the repair of DNA damage [34].…”
Section: Discussionmentioning
confidence: 57%
“…Although PTEN has no direct role in ATM/ATR activation, it may affect the functions of downstream repair proteins [3]. Because catalytic inhibitors of topoisomerases I and II inhibit the relaxation of helical super coiling during the replication process and induce DNA repair responses [17,19,24,35], PTEN may be induced by 3EZ, 20Ac-ingenol. Accordingly, PTEN was upregulated after 3 h of treatment with 3EZ, 20Ac-ingenol in BALL-1 cells, and inhibition of the PI3K/Akt signaling pathway was almost concomitant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations